Las relaciones entre Chupícuaro y el Centro de México durante el Preclásico reciente. Una crítica de las interpretaciones arqueológicas - Véronique Darras (Journal de la Société des Américanistes)
The relationships between Chupicuaro and the Central Highlands of Mexico during Late Formative Period. A reappraisal of the archaeological interpretations. Since more than fifty years, the stylistic analogies observed between the Chupicuaro and Central Highlands cultures, and the supposed influent role of Chupicuaro, appeared as the paradigm which has structured most of the models which reconstitute the Late Formative cultural processes in both regions. To explain the similarities, these models generally refer to population movements, influences of varied nature, and/or comercial relationships. A methodic reappraisal of the scientific background reveals that in several cases, the nature of the archaeological record is not able to support rigorously the proposed perspectives. After revisiting briefly the archaeological history of Chupicuaro, this article will reconstruct the conditions under which the diverses interpretations have been elaborated and how they evolutionated. This reappraisal permits to moderate the dominant position which is articulated around the idea of influence, and reveals all the complexity and width scales of relationships and interactions.